Effect of β-Aminobutyric Acid on Disease Resistance Against Rhizopus Rot in Harvested Peaches - Wang, Jing; Cao, Shifeng; Wang, Lei; Wang, Xiaoli; Jin, Peng; Zheng, Yonghua (Frontiers in Microbiology, 2018)
The effect of β-aminobutyric acid (BABA) on Rhizopus rot produced by Rhizopus stolonifer in harvested peaches and the possible action modes were investigated. Treatment with 50 mmol L-1 of BABA resulted in significantly lower lesion diameter and disease incidence compared with the control. The activities of defense-related enzymes chitinase and β-1,3-glucanase were notably enhanced by this treatment. Meanwhile, BABA treatment also increased lignin accumulation and maintained higher energy status in peaches by enhancing activities of enzymes in the phenylpropanoid and energy metabolism pathways. Semiquantitative reverse transcription-PCR (RT-PCR) results indicated that the transcription of four defense-related genes was substantially and rapidly enhanced only in that BABA-treated fruit upon inoculation with the pathogen. Thus, our results demonstrated that BABA was effective on controlling Rhizopus rot by inducing disease resistance, which includes the increase in gene transcription and activity of defense-related enzymes, the enhancement of cell wall strength and the maintenance of high energy status in Prunus persica fruit. Moreover, the disease resistance induced by BABA was demonstrated through priming model rather than direct induction.